(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2024)
Background: Menstruation is the culmination of a collection of changes that arise due to a series of interactions between the cerebrum, hypothalamus, pituitary gland, adrenal cortex, thyroid gland in the body. These changes cause symptoms that usually occur 7-10 days before menstruation called Premenstrual Syndrome. Symptoms such as flatulence, irritability, anxiety, difficulty sleeping and difficulty concentrating that was result in negative behavior. Objective: To determine the relationship between pain and behavior in dealing with Premenstrual Syndrome (PMS) in young women in the working area of the Mekarpura Health Center, Kotabaru District. Method: Analitic survey method. The population in this study were all 90 adolescent. The sample used porpusive sampling of 47 research respondents in February 2023. Data collection used a questionnaire which was analyzed in the form of computer programe. Results: Most of the pain in Premenstrual Syndrome (PMS) in young girls was even more painful as many as 19 people (40.4%), the category of behavior dealing with Premenstrual Syndrome (PMS) in young women was negative as many as 31 people (66%). There is a relationship between pain and behavior in dealing with Premenstrual Syndrome (PMS) in young women in the working area of the Mekarpura Health Center, Kotabaru District (p value = 0.000 <0.05). Conclusion: There is a relationship between pain and behavior in dealing with Premenstrual Syndrome (PMS) in young women in the working area of ​​the Mekarpura Health Center, Kotabaru District.